2022
DOI: 10.1101/2022.06.30.22277105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real World Evidence of Effectiveness of COVID-19 Vaccines and Anti SARS-CoV-2 Monoclonal Antibodies Against Post-Acute Sequelae of SARS-CoV-2 Infection

Abstract: Background: We evaluated the effectiveness of COVID-19 vaccines and monoclonal antibodies (mAb) against Post-Acute Sequelae of SARS-CoV-2 infection (PASC), an emerging public health problem. Methods and Findings: In a retrospective cohort study, we identified patients with clinically significant PASC using a COVID-19 specific, electronic medical record-based surveillance and outcomes registry from an 8-hospital tertiary healthcare system in the greater Houston metropolitan (primary analyses). Analyses were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…There is substantial heterogeneity between existing studies evaluating the effects of vaccination on PCC. 6 Our findings together with those from others imply that vaccination may reduce the risk of PCC by up to 50%, 79,12,13,1517 with an estimated relative risk reduction of 52% among Omicron-infected, and 35% among Delta-infected in our study. Despite important differences in study populations, study designs, analytical methods, and definitions of PCC across existing studies, our estimates are in line with previous evidence, albeit of smaller magnitude compared with one other study simultaneously investigating differences between SARS-CoV-2 variants and prior vaccination among non-hospitalised healthcare workers.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…There is substantial heterogeneity between existing studies evaluating the effects of vaccination on PCC. 6 Our findings together with those from others imply that vaccination may reduce the risk of PCC by up to 50%, 79,12,13,1517 with an estimated relative risk reduction of 52% among Omicron-infected, and 35% among Delta-infected in our study. Despite important differences in study populations, study designs, analytical methods, and definitions of PCC across existing studies, our estimates are in line with previous evidence, albeit of smaller magnitude compared with one other study simultaneously investigating differences between SARS-CoV-2 variants and prior vaccination among non-hospitalised healthcare workers.…”
Section: Resultssupporting
confidence: 81%
“…6 Several studies have been conducted using different study designs and populations, with the majority finding that the risk of PCC is approximately halved in vaccinated compared to non-vaccinated individuals. [7][8][9][10][11][12][13][14][15][16][17] While most studies evaluated symptoms persisting for more than four weeks 8,9,17 or more than 12 weeks 10,12,13,15,16 after SARS-CoV-2 infection, only three assessed symptoms beyond six months and identified a lower 7 or no 11,14 risk reduction with vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial heterogeneity between existing studies evaluating the effects of vaccination on PCC [ 5 ]. Our findings together with those from others imply that vaccination may reduce the risk of PCC by up to 50% [ 6 8 , 11 , 12 , 14 16 ], with an estimated reduction in the odds of 52% among Omicron-infected, and 35% among Delta-infected in our study. Despite important differences in study populations, study designs, analytical methods, and definitions of PCC across existing studies, our estimates are in line with previous evidence, albeit of smaller magnitude compared with one other study simultaneously investigating differences between SARS-CoV-2 variants and prior vaccination among non-hospitalised healthcare workers [ 8 ].…”
Section: Discussionsupporting
confidence: 83%
“…Current evidence suggests that the risk of PCC is relevantly reduced by vaccination with SARS-CoV-2 vaccination [5]. Several studies based on different designs and populations found that the risk of PCC is approximately halved in vaccinated compared to non-vaccinated individuals [6][7][8][9][10][11][12][13][14][15][16]. While most evaluated symptoms persisting for more than four [7,8,16] to 12 weeks [9,11,12,14,15] after SARS-CoV-2 infection, few assessed symptoms beyond six months and found a lower [6] or no [10,13] risk reduction with vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Promoting a fast recovery from these immunological imbalances after SARS-CoV-2 infection resolves or early in PASC, could be crucial to disrupting the foundational steps that lead to long-term PASC outcomes. Indeed, recent studies indicate that SARS-CoV-2 vaccination associated with a faster recovery can reduce the incidence of PASC (144)(145)(146). Likewise, the early use of antivirals might also be used to prevent PASC, given the relationship between high SARS-CoV-2 RNAemia and PASC (147).…”
Section: Closing Remarksmentioning
confidence: 99%